Praksis Praktikum Fisika Mode Daring: Studi Kasus Pembelajaran di SMA/MA Jawa Tengah dan Jawa Timur Semasa Pandemi Covid-19 (UPEJ Unnes Physics Education Journal, 2020)
This study aims to describe teachers' perceptions of practicum in physics learning, the implementation and obstacles of implementing physics practicum in online learning during the Covid-19 pandemic in the even semester of the 2019/2020 academic year and the odd semester of the 2020/2021 academic year. The research method is descriptive quantitative. The instrument used was a google form questionnaire. Samples were taken using simple random sampling technique, obtained 50 SMA / MA physics teachers in Central Java and East Java. The results showed that all teachers have the same perception that the application of practicum in learning physics is important. However, during the online learning period the teachers rarely applied practicum. Some teachers even argue that they haven't thought about how to implement online practicum. More than 50% of teachers have tried to do practicum during online learning. The types of practicum used are various, ranging from virtual laboratories, simulations, video demonstrations and hands-on. The implementation of practicum in online learning experiences various obstacles, both hardware (practicum material tools, computers / notebooks, smartphones, networks) and software, namely practicum procedures that are not understood by students and students' activeness control mechanisms.